Industrial Policy and Planning - Planning Commission (Planning Commission, 1953)
India's industrial policy and planning framework emphasizes a balanced approach to economic development, combining state-controlled key sectors with regulated private enterprise. The Industrial Policy Resolution of 1948 and subsequent planning machinery under the Industries (Development and Regulation) Act, 1951, aimed to enhance industrial output, prioritize core and consumer goods, and modernize production capabilities. Special focus was given to small-scale and cottage industries to promote employment and inclusive growth. Financial investments, both domestic and foreign, supported infrastructure, modernization, and skill development initiatives. Initial progress reports demonstrated significant achievements in production targets and industrial projects, setting a foundation for sustained growth, self-reliance, and a resilient industrial landscape.
India Publication Division
India Publication Division
Keywords: Industrial Policy; Five-Year Plans; Small-Scale Industries; Cottage Industries; Industrial Planning; Consumer Goods; Producer Goods; Public and Private Sector Investment; Industrial Development; Economic Self-Reliance